Educational institutions in Egypt during the reign of the first Mamluk state (658-784 Ah-1250-1382 ad) - scientific beacons and cultural and educational monuments- - amroun, Abd ar-Rahmân; charef, khaled (The Algerian Historical Journal, 2026)
If, according to educationalists, the educational process is based on three basic axes, namely the teacher, the learner and the educational curriculum, then there is no doubt that the role of Science and educational institutions is an integral part of this educational system, but without them the process becomes difficult, which is why the maritime Mamluk state realized-the first- The importance of these educational facilities, so I worked to establish them taking into account the Sunni gradient and the different educational stages. boys under fifteen study in the manuals, and then at another stage they move to the science seminars in mosques. if a student wants to learn more from various sciences, he goes to schools with specialization and scientific diversity. there are fiqhi schools according to the four madhhabs, schools of Hadith, schools containing councils of language, grammar, reading, etc. there are also scientific institutions no less important than the above, such as and the gorges that share the common of being a shelter for the class of worshipers and ascetics In this article, we will try to uncover these scientific edifices and their role in graduating the scientific and educated elites in society.